PENGARUH SUKU BUNGA BANK INDONESIA (SBI) DAN JUMLAH UANG BEREDAR (JUB) TERHADAP INFLASI DI INDONESIA PERIODE 2015-2017 - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
As for the conclusions of this study, namely The interest rate has no effect on the inflation rate because the process of transmitting monetary policy through interest rates to aggregate demand has not been fully implemented. The fluctuating increase in interest rates can make it difficult for businesses to pay interest expenses and obligations. High interest rates will increase the company's burden, so that it will directly reduce the company's profit. Correcting the inflation problem in Indonesia, if only carried out with short-term monetary instruments, will not be sufficient to solve the inflation problem.The results of this study indicate that the Bank Indonesia interest rate has no effect on inflation in Indonesia. This is indicated by the results of the t value <t table, namely 1.121<1.693 and a significant value of 0.27> 0.05. Money is anything that can be used / received to make payments for goods, services or debt.